2021
DOI: 10.1111/cea.14027
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end product intake during pregnancy and offspring allergy outcomes: A Prospective cohort study

Abstract: Background:Associations have been shown between concurrent assessment of dietary intake of advanced glycation end products (AGEs) and childhood allergic outcomes. We examined the association between maternal AGEs intake and development of offspring asthma, wheeze, atopic dermatitis, allergic rhinitis and food allergies, and sought to determine whether the intake of AGEs was associated with cord sera cytokines/chemokines. Methods: Pregnant women ≥16 years were recruited in the Healthy Start study, a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…For example, maternal allergy – and hence presumably an altered in utero environment – has an additional effect on risk of allergy in the offspring 30 . Evidence for the in utero origins of asthma comes from associations of childhood asthma with maternal pre‐natal conditions and exposures such as maternal age, diet, smoking, infectious illness, stress, weight gain and exposure to farm animals 21,31,32 . The detection of asthma‐associated differential epigenetic programming in neonates also supports the possibility that asthma might originate in utero 33–35 …”
Section: Developmental Programming and Early Life Origins Of Diseasementioning
confidence: 91%
“…For example, maternal allergy – and hence presumably an altered in utero environment – has an additional effect on risk of allergy in the offspring 30 . Evidence for the in utero origins of asthma comes from associations of childhood asthma with maternal pre‐natal conditions and exposures such as maternal age, diet, smoking, infectious illness, stress, weight gain and exposure to farm animals 21,31,32 . The detection of asthma‐associated differential epigenetic programming in neonates also supports the possibility that asthma might originate in utero 33–35 …”
Section: Developmental Programming and Early Life Origins Of Diseasementioning
confidence: 91%
“…While it might be of clinical relevance, this finding was not statistically significant in an adjusted model [36]. Data from the same cohort study showed that maternal intake during pregnancy of advanced glycation end products (AGEs), which are contained in foods typical of the Western diet, such as burgers and fried foods, was not associated with offspring asthma and allergy outcomes up to age eight [37]. Other observational studies found either no significant association between maternal diet quality during pregnancy and asthma at 10 years old [38] or even a protective effect of a maternal Western diet pattern in pregnancy on the risk of childhood wheezing [39].…”
Section: Maternal Dietary Patternsmentioning
confidence: 98%
“…It was thus showed that exposure to AGEs through children's diet is associated to allergic outcomes. However, no association was found between maternal AGEs intake during pregnancy and allergic outcomes in offspring (Venter et al, 2021). The mechanisms therefore appear to be complex and further studies are needed to understand how AGEs can influence the allergic response.…”
Section: Maillard Reaction Products and Allergiesmentioning
confidence: 98%